2019
DOI: 10.1111/jfpe.13265
|View full text |Cite
|
Sign up to set email alerts
|

Detection of adulterants and authenticity discrimination for coarse grain flours using NIR hyperspectral imaging

Abstract: Near‐infrared (NIR) hyperspectral imaging combined with multivariate analyses were used to execute adulterants detection and authenticity discrimination for coarse grain flours including millet, corn, and soybean. Spectral data in the range of 865–1,711 nm were first extracted and preprocessed from a total of 1,080 samples of six categories of pure and adulterated flours. Principal component analysis was employed to generate scores scatter plots for differentiating specific grouping of samples. Successive proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As a special spectroscopic technique, HSI is also gradually being developed in the food authenticity field, primarily employing NIR and VIS-NIR for breeds or species identification in plant-derived products in recent years. Shao et al (2019) used NIR-HSI to identify millet, corn, and soybean binary mixtures and their pure samples. The PLS-DA results based on the selected effective wavelengths and full spectra showed that the discrimination rates of all the models exceeded 94.8%.…”
Section: Principle and Research Progress In Rapid Analysis Technologymentioning
confidence: 99%
“…As a special spectroscopic technique, HSI is also gradually being developed in the food authenticity field, primarily employing NIR and VIS-NIR for breeds or species identification in plant-derived products in recent years. Shao et al (2019) used NIR-HSI to identify millet, corn, and soybean binary mixtures and their pure samples. The PLS-DA results based on the selected effective wavelengths and full spectra showed that the discrimination rates of all the models exceeded 94.8%.…”
Section: Principle and Research Progress In Rapid Analysis Technologymentioning
confidence: 99%
“…Bai et al (2020) used hyperspectral imaging combined with principal component analysis and clustering analysis to detect the adulteration of sorghum, and the detection accuracy reached 91%. Shao et al (2019) used hyperspectral imaging combined with multivariate analysis to detect the adulteration of millet, corn, and soybean powder, and the detection accuracy was above 94.8%. Laborde et al (2021) successfully detected the adulteration of peanut powder in chocolate powder by using hyperspectral imaging combined with stoichiometry.…”
Section: Introductionmentioning
confidence: 99%